Diagnostic performance of Elecsys immunoassays for cerebrospinal fluid Alzheimer's disease biomarkers in a nonacademic, multicenter memory clinic cohort: The ABIDE project. Issue 1 (11th September 2018) - Willemse, Eline A.J.; van Maurik, Ingrid S.; Tijms, Betty M.; Bouwman, Femke H.; Franke, Andreas; Hubeek, Isabelle; Boelaarts, Leo; Claus, Jules J.; Korf, Esther S.C.; van Marum, Rob J.; Roks, Gerwin; Schoonenboom, Niki; et al.
Abstract: Introduction: We compared the automated Elecsys and manual Innotest immunoassays for cerebrospinal fluid (CSF) Alzheimer's disease biomarkers in a multicenter diagnostic setting. Methods: We collected CSF samples from 137 participants in eight local memory clinics. Amyloid β(1–42) (Aβ42), total tau (t‐tau), and phosphorylated tau (p‐tau) were centrally analyzed with Innotest and Elecsys assays. Concordances between methods were assessed. Results: Biomarker results strongly correlated between assays with Spearman's ρ 0.94 for Aβ42, 0.98 for t‐tau, and 0.98 for p‐tau. Using Gaussian mixture modeling, cohort‐specific cut‐points were estimated at 1092 pg/mL for Aβ42, 235 pg/mL for t‐tau, and 24 pg/mL for p‐tau. We found an excellent concordance of biomarker abnormality between assays of 97% for Aβ42 and 96% for both t‐tau and p‐tau. Discussion: The high concordances between Elecsys and Innotest in this nonacademic, multicenter cohort support the use of Elecsys for CSF Alzheimer's disease diagnostics and allow conversion of results between methods. Highlights: Method comparison of 137 CSF samples collected in eight nonacademic memory clinics. Innotest and Elecsys strongly correlated: ρ = 0.94 Aβ42; 0.98 t‐tau; 0.98 p‐tau. Concordances of biomarker abnormalities: 97% Aβ42; 96% t‐tau and p‐tau. Concordance of NIA‐AA–based Alzheimer's disease profile (Aβ42 decreased and p‐tau increased): 89%. Preanalytical protocol deviations did not show effects on biomarker correlations.